Penetapan rendemen dan kandungan kimia ekstrak daun katuk (Sauropus androgynus (L.) Merr.) berdasarkan perbedaan metode pengeringan - Fara Azzahra (Sasambo Journal of Pharmacy, 2022)
Katuk leaves contain chemicals in the form of alkaloids, triterpenoids, saponins, tannins, polyphenols, glycosides and flavonoids, so they are widely used as antioxidants. One factor can affect in chemical content and yield extract is the drying method. The purpose of this study was to determine the effect of different drying methods on yield and chemical content of katuk leaf extract. This research method was experimental Posttest Only Design. Katuk leaves were dried using wind, oven, sun and continued by maceration with ethanol 96% as solvent. The macerate was filtered and air-dried to thick extract which was calculated yield and tested chemical content form of polyphenols, alkaloids, flavonoids, saponins, tannins and terpenoids. Yield data analysis was carried out using One Way ANOVA test. The average yield value of katuk leaf extract in the wind-dry drying method was 11.86±0.23%, the sun was 12.26±0.70%, the oven was 13.64±0.74%. One Way ANOVA test showed significant differences in wind and oven drying, sun and oven drying. Phytochemical screening of each drying showed the presence of polyphenols, alkaloids, flavonoids, saponins, tannins and triterpenoids. The conclusion of this study was that the drying method affects the yield of katuk leaf extract but has no effect on chemical content.